Supporting the creation of hybrid museum experiences - Koleva, Boriana; Rennick-Egglestone, Stefan; Schnädelbach, Holger; Glover, Kevin; Greenhalgh, Chris; Rodden, Tom; Dade-Robertson, Martin (ACM press, 2009)
This paper presents the evolution of a tool to support the rapid prototyping of hybrid museum experiences by domain professionals. The developed tool uses visual markers to associate digital resources with physical artefacts. We present the iterative development of the tool through a user centred design process and demonstrate its use by domain experts to realise two distinct hybrid exhibits. The process of design and refinement of the tool highlights the need to adopt an experience oriented approach allowing authors to think in terms of the physical and digital “things” that comprise a hybrid experience rather than in terms of the underlying technical components.